Are children at schools registered to The Daily Mile™ more physically active?. (20th October 2021) - Venkatraman, T; Honeyford, K; van Sluijs, EMF; Costelloe, C; Saxena, S
Abstract: Background: The Daily Mile (TDM) is among the most popular school-based running programmes recommended globally by governments and the WHO to meet the shortfalls in children's physical activity. In England, it has been adopted by 1 in 5 primary schools. However, its impact on children's physical activity has not been assessed at scale. We aimed to compare a)minutes (mins) of moderate to vigorous physical activity (MVPA) in and outside school hours and b)meeting physical activity guidelines in primary school children in England, comparing those in schools registered with TDM with those that were not. Methods: This was a cross-sectional study. We used self-reported data of 49, 561 English primary school children(5-11 years) from the Active Lives Children and Young People Survey and TDM registration data of their school. We compared mins of MVPA in and outside school hours between children in TDM-registered and non-registered schools using a multilevel zero-inflated negative binomial model; and the differences in the likelihood of meeting physical activity guidelines based on TDM registration with a multilevel logistic regression model. All models included a random effect for school and adjusted for potential confounders. Results: Children attending TDM-registered schools reported an extra 36 mins of MVPA a week overall, including 10 additional mins (95%CI:3, 16) MVPA/week during school hours and 26 additional (95%CI:4, 44) mins MVPA/week outside school hours. Children in TDM-registered schools were 6% more likely to meet physical activity guidelines compared to those who were not(RR:1.06 (95%CI:1.02, 1.11)). Conclusions: Children in primary schools registered to TDM report more physical activity that is not compensated for outside school hours. However, the absolute differences fall considerably short of international guidelines across the whole child population. Therefore, a whole school and systems-based approach is required, embedding school-based running programmes. Key messages: Children in schools registered to TDM report more MVPA overall, inside, and outside school hours; suggesting no compensation of activity in those who are registered. TDM is a potential solution to increase children's physical activity during the school day.